PERAN RELAWAN TEKNOLOGI INFORMASI DAN KOMUNIKASI ACEH DALAM MENINGKATKAN KEMAMPUAN LITERASI DIGITAL MASYARAKAT DI ERA DIGITAL SOCIETY - Hijrah; M. Rezki Andhika (Prodi Teknologi Pendidikan Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
This research was conducted with the aim of finding out the role and obstacles faced by the Aceh ICT Volunteer group in increasing the digital literacy of the Acehnese people. Data collection in this research was carried out using a qualitative approach with information sources obtained from the Aceh ICT Volunteer group using interview techniques, as well as making observations. directly at several Saweu Gampong activities which are activities that are often carried out by the Aceh ICT Volunteer group in an effort to increase community digital literacy. Documentation studies were also carried out to obtain more sources of information. In this research, the triangulation method was also used to obtain the reliability of the data that will be used as research results later. The results of the research that has been carried out find that the role of Aceh ICT Volunteers is quite good with saweu gampong activities, but more massive promotion using social media is needed to increase public interest, while the obstacle faced is that the digital gap in the Aceh province region is still large which has a decreasing impact. Aceh province digital literacy index.